A framework for addressing Alzheimer's disease: Without a frame, the work has no aim. Issue 4 (8th December 2022) - Ball, Daniel E.; Mattke, Soeren; Frank, Lori; Murray, James F.; Noritake, Ryoji; MacLeod, Timothy; Benham‐Hermetz, Samantha; Kurzman, Alissa; Ferrell, Phyllis
Abstract: Confronting Alzheimer's disease (AD) involves patients, healthcare professionals, supportive services, caregivers, and government agencies interacting along a continuum from initial awareness to diagnosis, treatment, support, and care. This complex scope presents a challenge for health system transformation supporting individuals at risk for, or diagnosed with, AD. The AD systems preparedness framework was developed to help health systems identify specific opportunities to implement and evaluate focused improvement programs. The framework is purposely flexible to permit local adaptation across different health systems and countries. Health systems can develop solutions tailored to system‐specific priorities considered within the context of the overall framework. Example metric concepts and initiatives are provided for each of ten areas of focus. Examples of funded projects focusing on screening and early detection are provided. It is our hope that stakeholders utilize the common framework to generate and share additional implementation evidence to benefit individuals with AD.